Multicultural implications of restorative justice: Potential pitfalls and dangers - (:unkn) unknown (My University, 2016)
The article The Multicultural Implications of RestorativeJustice: Potential Pitfalls and Dangers informs practitioners about concerns regarding the implementation of such frameworks when working with persons of crosscultural perspectives. This document examines concerns practitionersof restorative justice must keep inmind when working with people fromdifferent cultures. Efforts to addressthese concerns must deal with challengesfull of potential dangers and pitfalls.People from different cultures have differentways of speaking and behaving. Inaddition, a person’s cultural milieu determineshis or her world view, perceptionof justice, and communication style